2017
DOI: 10.1021/jacs.6b10140
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Anion Delocalization on Electron Transfer in a Covalent Porphyrin Donor–Perylenediimide Dimer Acceptor System

Abstract: Photodriven electron transfer from a donor excited state to an assembly of electronically coupled acceptors has been proposed to enhance charge transfer efficiency in functional organic electronic materials. However, the circumstances under which this may occur are difficult to investigate in a controlled manner in disordered donor-acceptor materials. Here we investigate the effects of anion delocalization on electron transfer using zinc meso-tetraphenylporphyrin (ZnTPP) as a donor and a perylene-3,4:9,10-bis(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
47
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 76 publications
4
47
2
Order By: Relevance
“…In previous reports, we have revealed that PBI-R H-aggregates ( RA ) show ultrafast exciton migration processes in sub-50 fs with the subsequent formation of an excimer state with the time constant of 250 fs in nonpolar methylcyclohexane (MCH). , The excimer state is considered as a low-lying trap state induced by exciton localization and structural relaxations within H-aggregates. , In this report, with two monomers ( RM and OM ) and RA as the reference system, we have focused on the observation and characterization of the delocalized charge-separated state in PBI-OR H-aggregate ( OA ) in MCH. Especially, the delocalized charges and the charge transfer (transport) in OA were corroborated by comparing with the excited-state experimental results in both electronic and vibrational regimes with the CS process of the reference monomer ( OM ) that only exhibits the typical intramolecular electron transfer process from the substituents to the PBI core in the excited state. , We confirmed that the charge delocalization in OA induces efficient CS (two times) and slower charge recombination (CR) (four times) processes compared with the intramolecular CS process of OM . The latter may originate from the molecular rigidity and spatial separation through transport of an electron/hole in H-aggregates.…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…In previous reports, we have revealed that PBI-R H-aggregates ( RA ) show ultrafast exciton migration processes in sub-50 fs with the subsequent formation of an excimer state with the time constant of 250 fs in nonpolar methylcyclohexane (MCH). , The excimer state is considered as a low-lying trap state induced by exciton localization and structural relaxations within H-aggregates. , In this report, with two monomers ( RM and OM ) and RA as the reference system, we have focused on the observation and characterization of the delocalized charge-separated state in PBI-OR H-aggregate ( OA ) in MCH. Especially, the delocalized charges and the charge transfer (transport) in OA were corroborated by comparing with the excited-state experimental results in both electronic and vibrational regimes with the CS process of the reference monomer ( OM ) that only exhibits the typical intramolecular electron transfer process from the substituents to the PBI core in the excited state. , We confirmed that the charge delocalization in OA induces efficient CS (two times) and slower charge recombination (CR) (four times) processes compared with the intramolecular CS process of OM . The latter may originate from the molecular rigidity and spatial separation through transport of an electron/hole in H-aggregates.…”
Section: Introductionsupporting
confidence: 59%
“…The intermolecular interactions create new coupled states, which correspond to the delocalized exciton or charge-separated states, contrary to simple monomeric states. Moreover, many reports proposed that aggregates forming the delocalized states induce efficient exciton transport or charge separation (CS) processes by coherent interactions. Since these interactions can be varied according to the intermolecular geometry of aggregates, delocalized states are strongly dependent on intra- and/or intermolecular vibrations.…”
Section: Introductionmentioning
confidence: 99%
“…However, most ladder‐type molecules typically exhibit electron‐rich characteristics and the synthesis of electron‐deficient analogues remains a great challenge because of the reduced chemical reactivity and unfavored steric hindrance created by typical electron‐withdrawing substituents . Hence it is highly imperative to develop electron‐deficient ladder‐type π‐conjugated systems, which are highly desired for constructing donor‐acceptor dyads and developing organic semiconductors using the donor‐acceptor strategy …”
Section: Figurementioning
confidence: 99%
“…[29][30][31] However,i ts till remains instructive to develop more efficienta nd viable strategies to construct supramolecular discrete p stacksb ased on flexible p frameworks. [32][33][34][35][36][37][38][39] To this end, we soughtt oi ntroduce orthogonal intramolecular p NDI •••p NDI interactions [40][41][42][43] and hydrogen bonding [44,45] to shapef lexible and discrete p stacks in the NDI system.…”
Section: Introductionmentioning
confidence: 99%
“…Würthner and co‐workers have reported discrete π stacks in the aggregation of the related family of perylenediimides, based on the foldamer approach . However, it still remains instructive to develop more efficient and viable strategies to construct supramolecular discrete π stacks based on flexible π frameworks . To this end, we sought to introduce orthogonal intramolecular π NDI ⋅⋅⋅ π NDI interactions and hydrogen bonding to shape flexible and discrete π stacks in the NDI system.…”
Section: Introductionmentioning
confidence: 99%